Perspectives on Leadership in Early Childhood Education and Care Centers Through Community of Practice - Kirsi-Marja Heikkinen; Raisa Ahtiainen; Elina Fonsén (SAGE Open, 2022)
This article investigates early childhood education and care (ECEC) leadership through the concept of community of practice (COP). The focus is on ECEC leaders’ perceptions regarding their leadership during the educational changes taking place in the context of Finnish ECEC. The purpose is to increase understanding of how leaders see themselves in relation to the ECEC multi professional working community and practices of distributed leadership. The data are five focus group interviews of ECEC leaders analyzed with directed content analysis within the theoretical frame of domain, practice, and community forming the core of COP in Lave and Wenger. The results show how all three COP components comprise several dimensions in ECEC leaders’ perceptions of their leadership. For example, the component of the leadership domain consists of ECEC values, ECEC legislation, and ECEC curriculum. The results indicate that a formal leadership role is essential in leading the community and its vision. Moreover, building flexible leadership structures and supporting multi professional cooperation in the community augment leadership as a community’s joint enterprise.